2018
DOI: 10.1016/j.molcel.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Mettl1/Wdr4-Mediated m7G tRNA Methylome Is Required for Normal mRNA Translation and Embryonic Stem Cell Self-Renewal and Differentiation

Abstract: tRNAs are subject to numerous modifications, including methylation. Mutations in the human N-methylguanosine (mG) methyltransferase complex METTL1/WDR4 cause primordial dwarfism and brain malformation, yet the molecular and cellular function in mammals is not well understood. We developed mG methylated tRNA immunoprecipitation sequencing (MeRIP-seq) and tRNA reduction and cleavage sequencing (TRAC-seq) to reveal the mG tRNA methylome in mouse embryonic stem cells (mESCs). A subset of 22 tRNAs is modified at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
363
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(373 citation statements)
references
References 40 publications
10
363
0
Order By: Relevance
“…In mESCs, the global m 7 G tRNA methylome is essential for appropriate translation of cell cycle genes and genes associated with brain malformation. Further to this observation, Mettl1 or Wdr4 knockout causes defective mESC self-renewal and neural lineage differentiation [103]. This study has clearly demonstrated the tRNA m 7 G methylome in mammals and shown the critical nature of METTL1 and WDR and m 7 G modification in regulation of stem cells and disease.…”
Section: Involvement Of Trna M 7 G46 Methyltransferase In Diseasessupporting
confidence: 62%
See 2 more Smart Citations
“…In mESCs, the global m 7 G tRNA methylome is essential for appropriate translation of cell cycle genes and genes associated with brain malformation. Further to this observation, Mettl1 or Wdr4 knockout causes defective mESC self-renewal and neural lineage differentiation [103]. This study has clearly demonstrated the tRNA m 7 G methylome in mammals and shown the critical nature of METTL1 and WDR and m 7 G modification in regulation of stem cells and disease.…”
Section: Involvement Of Trna M 7 G46 Methyltransferase In Diseasessupporting
confidence: 62%
“…Amino acid substitution of WDR4 has been revealed as the cause mutation [101,102] The molecular mechanism of microcephaly has not been well understood. In order to profile the m 7 G tRNA methylome in mouse embryonic stem cell (mESCs), two independent methods have been developed: m 7 G methylated immunoprecipitation sequencing (MeRIP-seq) and tRNA reduction and cleavage sequencing (TRAC-seq) [103]. In mESCs, the global m 7 G tRNA methylome is essential for appropriate translation of cell cycle genes and genes associated with brain malformation.…”
Section: Involvement Of Trna M 7 G46 Methyltransferase In Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…m7G also occurs internally within human cytoplasmic tRNA and 18S-rRNA, installed by METTL1-WDR4 [87], a m7G "writer" complex, which is similar to m6A complex, and WBSCR22 [88,89], respectively. These internal m7G modifications impact RNA processing and function, especially mRNA translation [85,90]. However, its existence and distribution within miR-NAs or lncRNAs remain to be investigated.…”
Section: -Methylguanosine (M7g)mentioning
confidence: 99%
“…m 7 G METTL1 and WDR4 are both necessary for the introduction of the 7-methylguanosine at position 46 [34]. In 2018, Lin et al have reported that METTL1 knockdown reduces the m 7 G fraction, which causes tRNA destabilization and ribosome pausing at m 7 G tRNA-dependent codons that leads to a decrease in translation [35]. Overexpression of METTL1 in hepatocellular carcinoma has been shown to promote cell proliferation and migration, and to lead to poor prognosis in HCC [36].…”
Section: Transfer Rnamentioning
confidence: 99%